Pengaruh Likuiditas, Total Asset Turnover dan Earnings Quality terhadap Firm Value dengan Tax Planning sebagai Pemoderasi pada Perusahaan Properti dan Real Estate di BEI - Tambun, Sihar; Ferawati, Ferawati; Sitorus, Riris Rotua (Media Akuntansi Perpajakan, 2025)
This study aims to examine the effect of liquidity, total asset turnover, and earnings quality on firm value, as well as to analyze the moderating role of tax planning in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. The sampling method used is purposive sampling based on specific criteria, resulting in 30 companies as the research sample. Data were analyzed using panel data regression with the best model selected through Chow, Lagrange Multiplier, and Hausman tests, followed by classical assumption and hypothesis testing. The results indicate that liquidity and total asset turnover have a positive and significant effect on firm value, while earnings quality has no significant effect. Furthermore, tax planning strengthens the relationship between liquidity and firm value but does not strengthen the relationship between total asset turnover and earnings quality with firm value